Marketing channels and intermediaries in gurunagar fish market, jaffna, sri lanka - Shobiya, P.; Uventhikka, S.; Sivagini, K.; Amarathunga, A.M.H.D.; Gobykrishanth, R.; Fernando, A.S.R.; Sivashanthini, K. (Research Gate, 2020)
Gurunagar market is one of the busiest and prominent landing site fish market in Jaffna peninsula. It is vital to know the current status and marketing efficiency in order to enhance and develop the existing marketing system in Gurunagar. Thus, the present study was carried out to acquire knowledge on marketing intermediaries and their functions, marketing channels, market infrastructure and to recommend possible solutions for the identified limitations in Gurunagar fish market from July 2019 to December 2019. Qualitative method was designed to obtain data. Structured questionnaires were used to collect data from 104 fish marketers as well as direct observations and group discussions were employed on market infrastructures and the challenges faced by the fish intermediaries. Literature review from journals, books and reliable websites was conducted to gather secondary information. Results were characterized in the form of cognitive map, tables and figures. The key market actors found were fishermen, auctioneers, agents, dry fish producers, wholesalers, retailers and exporters. Throughout the study 07 types of marketing channels, a total 12 components and 16 connections were recorded. It is obvious that the marketing infrastructure facilities are poor in condition. The major challenges reported are less market space, poor storage, cooling facilities and sanitation, improper display and handling of fish, sorting, weighing and unhygienic condition. To overcome these issues all the intermediaries, government and non-governmental organizations need to take participatory actions together.
Keywords: Challenges; Infrastructure; Marketing efficiency